Precision and accuracy of the static GNSS system for surveying networks used in Civil Engineering (2018)
A field check was implemented for calibrating surveying equipment. It was geo-referenced with a Total Station Theodolite and by implementing procedures concerning repeatability and reproducibility. We carried out GNSS (Global Navigation Satellite System) static positioning with double frequency equipment, sensitizing occupation times, day times, uncorrected coordinates subjected to a differential correction procedure and type of coordinates obtained. This facilitated an evaluation of precision and accuracy for the GNSS positioning with the static method, which gave a global RMSE (root mean square error) of 1 cm for conditions with no multipath effect and 4 cm for field calibration points close to buildings. Additionally, optimal results for occupation times of 30 minutes were found, and the need to use planar Cartesian coordinates to ensure compatibility with the surveys using electronic measurement of distances, which allows the use of the static GNSS positioning for geo-referencing precise surveying networks, and can be used in different applications in Civil Engineering.